Examining The Effectiveness of Wordwall-Enhanced Gamification Learning Models on Student Engagement, Motivation, and Academic Performance in Economics Education - Maulana, Ade Rizki; Fahrurrozi, Muh. (Sumber Belajar Sejahtera, 2026)
: This study examines the impact of gamification learning model assisted by Wordwall media on students' learning interest, motivation, and achievement in Economics subject. Using quasi-experimental design with Non-Equivalent Control Group, 41 tenth-grade students at SMA Yadinu Masbagik were divided into experimental (21 students) and control groups (20 students). Data were collected using validated questionnaires for interest and motivation (10 items each) and achievement test (10 questions), with reliability α > 0.88. Analysis employed paired and independent sample t-tests, Cohen's d, and N-Gain scores using SPSS. Results showed significant improvements in the experimental group: learning interest increased 68.2% vs 33.3% (control), motivation 67.2% vs 30.1%, and achievement 56.4% vs 29.5%. All differences were statistically significant (p < 0.001) with large effect sizes (Cohen's d > 1.8) and high N-Gain scores (71.60%-76.19%). The gamification learning model assisted by Wordwall media proved highly effective in enhancing students' learning interest, motivation, and achievement in Economics education.